2004
DOI: 10.3989/scimar.2004.68n4501
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of the Caprellidea (Crustacea: Amphipoda) from the Strait of Gibraltar

Abstract: SUMMARY:The total fatty acid composition of nine species of caprellidean amphipods collected from the Strait of Gibraltar was investigated. All caprellids were characterised by high levels of polyunsaturated fatty acids, mainly eicosapentaenoic acid, 20:5(n-3), and docosahexaenoic acid, 22:6(n-3); other major fatty acids were the saturate palmitic acid, 16:0, and the monounsaturate oleic acid, 18:1(n-9). In spite of this general uniformity, univariate and multivariate analysis showed that Caprella acanthifera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
(26 reference statements)
4
20
0
5
Order By: Relevance
“…However, fish farming facilities such as ropes or buoys can support high densities of amphipods, especially caprellids, which are associated with fouling communities (Greene and Grizzle, 2007;Fernandez-Gonzalez and SanchezJerez, 2014). Caprellid amphipods are mainly detritivorous Tierno de Figueroa, 2009), andGuerra-García et al (2004) showed that caprellids generally present relatively high proportions of EPA and DHA, which agrees with our results in the control farm. In the active farm, significantly lower levels of DHA were found in C. equilibra, and of EPA in C. equilibra and C. dilatata, possibly due to a shift in diet, involving the greater consumption of feed wastes than in a natural diet (although the total fatty acid profile of C. equilibra showed no significant change between farms).…”
Section: Discussionsupporting
confidence: 94%
“…However, fish farming facilities such as ropes or buoys can support high densities of amphipods, especially caprellids, which are associated with fouling communities (Greene and Grizzle, 2007;Fernandez-Gonzalez and SanchezJerez, 2014). Caprellid amphipods are mainly detritivorous Tierno de Figueroa, 2009), andGuerra-García et al (2004) showed that caprellids generally present relatively high proportions of EPA and DHA, which agrees with our results in the control farm. In the active farm, significantly lower levels of DHA were found in C. equilibra, and of EPA in C. equilibra and C. dilatata, possibly due to a shift in diet, involving the greater consumption of feed wastes than in a natural diet (although the total fatty acid profile of C. equilibra showed no significant change between farms).…”
Section: Discussionsupporting
confidence: 94%
“…These differences were also observed in fatty acid-based nutritional analyses by Guerra-García et al (2004) and BaezaRojano et al (2014). Caprella grandimana consumed more diatoms and macroalgae than C. penantis, which is more carnivorous.…”
Section: Discussionsupporting
confidence: 56%
“…The level of 20:4n-6 is usually similar in males and females but the content of 20:5n-3 diVers among species and, for example, is higher in the testes of P. depressa and H. rubra but lower in those of A. purpuratus (Caers et al, 1999;Grubert et al 2004;Morais et al 2003). In several species of Caprellidea, we have also reported higher percentages of 16:1n-7 and lower levels of 18:0, 20:4n-6 and 20:5n-3 in females than in males (Guerra-García et al 2004). Sex diVerences in fatty acid composition of sea urchin gonads have only been Number of samples at La Herradura: 51.…”
Section: Discussionmentioning
confidence: 51%